Effect of ornament manipulations on following relations in male bearded reedlings. Issue 2 (2nd April 2016) - Tóth, Z.; Baldan, D.; Albert, C.; Hoi, H.; Griggio, M.
Abstract : Several studies have investigated how individuals' social status or behavioural and physiological traits affect social organisation in group-living species, but the potential role of ornamental traits has been rarely studied. Here, we analysed initiator–follower interactions in relation to experimentally manipulated sexually selected ornaments in captive flocks of male bearded reedlings ( Panurus biarmicus ). We manipulated beard length or tail length on the most and least frequently followed individuals in unisex flocks and examined how trait manipulation affected social prestige (i.e. frequency of being followed) and centrality (i.e. frequency of following others) of these individuals. We found that prestige/centrality after manipulation was significantly positively associated with their before-manipulation measure, whereas body condition did not affect social position within flocks. Similarly, the manipulation of the ornamental traits had no significant effect on the social positions of the manipulated individuals. Both social prestige and centrality were significantly positively correlated with the frequency of allopreening interactions, but not related to fighting success, i.e. the number of won/total fights in the flocks. Our findings indicate that the level of influence male bearded reedlings exert on social cohesion is not related to ornamental traits, and birds are likely to have a consistent social position, at least in the short term, within their flocks.